Student Engagement in Islamic Religious Education: Examining Jigsaw Cooperative Learning in Indonesian Secondary Schools - Ibra Abdillah; Raihana; Mohamad Firdaus Ahmad (CV Najmi Edu Creative, 2026)
This study aimed to examine the relationship between the Jigsaw cooperative learning model and student engagement in Islamic Religious Education among seventh-grade students at an Indonesian junior high school. The study applied a quantitative correlational design involving 70 students selected through saturated sampling. Data were collected using Likert-scale questionnaires and analyzed using normality testing and simple linear regression with SPSS version 22. The findings showed that the implementation of the Jigsaw cooperative learning model was rated high (88.97%), while student engagement was rated very high (90.84%). Regression analysis demonstrated a significant positive relationship between the Jigsaw cooperative learning model and pupil engagement (p < .05). The coefficient of determination (R² = .395) indicated that the Jigsaw cooperative learning model accounted for 39.5% of the variance in student engagement. This evidence shows that collaborative learning activities were positively associated with student engagement in Islamic Religious Education.